UPAYA PERLINDUNGAN HAK PENCIPTA DAN PENERJEMAH DI INDUSTRI KOMIK DIGITAL: Efforts to Protect the Rights of Creators and Translators in the Digital Comics Industry - Athaya Izzah Aqilah; Bustani, Simona (Reformasi Hukum Trisakti, 2025)
Intellectual Property Rights (IPR), including copyright, provide legal protection for creators and translators of creative works, such as digital comics. In the digital era, the challenges of copyright protection have escalated, particularly due to the ease of access that facilitates piracy. The problem of the study examines the protection of creators and translators of digital comics based on Indonesia’s Law No. 28 of 2014 and South Korea’s Copyright Act No. 17592, two significant markets for digital comics. The research employs a normative method with statutory and comparative legal approaches, using secondary data from primary and secondary legal sources. The result and conclusion reveal that while both countries share similarities in recognizing the moral and economic rights of creators and translators, there are differences in legal implementation. In Indonesia, recognition of translators' rights often depends on contractual agreements, whereas in South Korea, translators are recognized as independent creators. In conclusion, legal protections in both countries demonstrate a commitment to copyright, despite differences in approach and scope.